Karakteristik limbah medis padat dan pengelolaannya di Rumah Sakit Umum Daerah Manokwari - Ria Maria Come; Zita L Sarungallo; Meike M. Lisangan (Program Pascasarjana Universitas Papua, 2022)
Garbage is a waste or a byproduct of a business process or activity that is wasted negatively on living things and the environment. Solid medical waste can cause nosocomial infections. The aim of this research is to study the information on solid medical waste generated in Manokwari Hospital activities and medical stages based on the Republic of Indonesia Minister of Health Decree number 1204/MENKES/SK/X /2004. This research method is a qualitative descriptive study, using descriptive methods with survey techniques and observation. The waste observed in this study was solid medical waste generated from hospital activities, solid medical waste in the form of used syringes with an average value of 2.14 kg and bottles with an average value of 1.97 kg and gauze with an average value. -average 1.48 kg. The stages of medical waste management at Manokwari Hospital start from sorting, related, transporting, storing and destroying.